Germany's Technological Specialization Assures Growth Opportunities - Heike Belitz; Marius Clemens; Martin Gornig (Weekly Report, 2009)
Germany's economic profile gives reason to believe that the country will emerge strengthened from the current economic crisis. Germany boasts the world's highest share of value-added output attributable to (R&D) intensive goods and knowledge intensive services. At the same time, Germany possesses an extremely broad range of economic sectors that rely on R&D intensive goods and knowledge intensive services. German firms have strong competitive advantages in numerous industries, including vehicle manufacturing, chemicals, machine building, measurement and medical technologies, as well as business oriented services. Moreover, in relation to its important trading partners, Germany has a unique production portfolio. Although Germany's dependence on exports and specialization in the production of capital equipment has led to a sharp decline in demand in the current crisis, the country's orientation in R&D intensive technology represents a strong foundation for renewed growth as soon as the global economic climate improves. However, continued business investment in R&D during the recession is necessary if Germany hopes to emerge the crisis on sound footing-even if such investment does not generate revenues over the near term.
Keywords: O14; O33; O57; 330; Industrial specialization; Technological change